2018
DOI: 10.4149/neo_2018_171117n705
|View full text |Cite
|
Sign up to set email alerts
|

Aclidinium bromide inhibits human glioma cell proliferation, migration and invasion and promotes apoptosis via the PI3K/AKT signaling pathway

Abstract: This study investigates the anti-cancer potential of Aclidinium bromide (INN) in glioblastoma. Glioblastoma cell lines U251 and U87 were treated with INN and its effects on cell migration and invasion were assessed by transwell migration and invasion assays., The effects of INN on proliferation and apoptosis were detected by CCK-8 kit and flow cytometry, and Western blotting determined anti-apoptotic proteins and signaling pathway changes. The results show that INN effectively suppressed proliferation, migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…It is well known that Bcl-2 inhibits cell apoptosis through kinds of mechanisms [29]. Aclidinium bromide effectively induces apoptosis in U251 and U87 cells, and the antiapoptotic proteins Bcl-2, Cyclin D1, and p-AKT are decreased significantly [30]. Similarly, we found that siRNA siTM4SF1#1 and siTM4SF1#2 reduced the expression of CyclinD1 and Bcl-2, thus inducing cell cycle arrest and early apoptosis.…”
Section: Discussionsupporting
confidence: 58%
“…It is well known that Bcl-2 inhibits cell apoptosis through kinds of mechanisms [29]. Aclidinium bromide effectively induces apoptosis in U251 and U87 cells, and the antiapoptotic proteins Bcl-2, Cyclin D1, and p-AKT are decreased significantly [30]. Similarly, we found that siRNA siTM4SF1#1 and siTM4SF1#2 reduced the expression of CyclinD1 and Bcl-2, thus inducing cell cycle arrest and early apoptosis.…”
Section: Discussionsupporting
confidence: 58%
“…
With the in-depth studies on SIRT1 and other inflammatory response inhibitors in recent years, early monitoring and intervention on inflammatory response are expected in DN, thereby decreasing proteinuria (Huang et al, 2018). SIRT1 is a NAD + -dependent histone deacetylase, which is mainly distributed in mesangial cells, podocytes, renal tubular epithelial cells and renal interstitial cells in the kidney (Chen et al, 2017).
…”
mentioning
confidence: 99%